Analisis Kewajiban Akuntansi pada Lembaga Perkreditan Desa (LPD) Desa Adat Ungasan - Komang Ayu Shinta Mahayani; I Wayan Budi Satriya (UNHI Press, 2026)
This study's goal is to ascertain how the Bali Governor Regulation (PERGUB) Number 44 of 2017 is applied in the Ungasan Traditional Village Village Credit Institution's (LPD) financial reports. This study employed a qualitative research methodology. by employing techniques for gathering information from field data, paperwork, and interviews. The LPD in Ungasan Traditional Village has not fully complied with Bali Governor Regulation Number 44 of 2017 concerning financial reports, according to the study's findings. In the financial reports of the LPD of Ungasan Traditional Village, there are only balance sheets, profit and loss reports, LPD fund placement reports, activity reports, and LPD development reports. There are incomplete financial reports in the quarterly and annual reports. In preparing these financial reports, the Ungasan Traditional Village LPD should implement Bali Governor Regulation Number 44 of 2017 to ensure that its operations align with its objectives.